Processing Connectives with a Complex Form-Function Mapping in L2: The Case of French “En Effet” - Zufferey, Sandrine; Gygax, Pascal M. (Frontiers in Psychology, 2017)
Discourse connectives are often reported to be difficult for second language learners, yet the causes of these difficulties are still not fully understood. In this paper, we test the ability of German-speaking learners to process and understand a connective with a complex form-function mapping in their L2-French, namely ‘en effet’, a connective that does not have an exact translation equivalent in their L1-German. We assess learners’ competence both in an on-line processing experiment and an off-line judgment task. We argue that one of the interesting specificities of ‘en effet’ is that the two coherence relations that it conveys cannot equally be conveyed implicitly. This case study therefore provides some information about advanced learners’ sensitivity to the necessity of explicitly marking a coherence relation by the use of a connective. Our results indicate that advanced learners do not perceive the difference between relations that need and need not be marked by a discourse connective and have not acquired the complex form-function mapping of ‘en effet’. We argue that these difficulties cannot be attributed to negative transfer effects, but reflect general limitations in proficiency.